2019
DOI: 10.2136/vzj2018.08.0146
|View full text |Cite
|
Sign up to set email alerts
|

How Meaningful are Plot‐Scale Observations and Simulations of Preferential Flow for Catchment Models?

Abstract: Core Ideas We tested a range of dual‐permeability parameterizations at plot and catchment scale. Well‐performing parameters at plot scale did not clearly improve catchment simulation. Vertical preferential flow was important for simulating plot‐scale observations. At catchment scale, it appeared more important to consider fast lateral subsurface flow. This showed that different nonuniform flow processes are critical at different scales. Despite ubiquitous field observations of nonuniform flow processes, pref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 67 publications
(185 reference statements)
1
45
0
Order By: Relevance
“…The results of our study corroborate the findings of Glaser et al (). They showed that the transfer of dual‐permeability parameters from plot to catchment scale simulations did not improve discharge simulations and reasoned that vertical preferential flow does not seem to be of major relevance for catchment scale runoff generation in the Weierbach catchment.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The results of our study corroborate the findings of Glaser et al (). They showed that the transfer of dual‐permeability parameters from plot to catchment scale simulations did not improve discharge simulations and reasoned that vertical preferential flow does not seem to be of major relevance for catchment scale runoff generation in the Weierbach catchment.…”
Section: Discussionsupporting
confidence: 93%
“…We carried out this study in a headwater section (6 ha) of the Weierbach catchment, located in western Luxembourg, where Glaser, Jackisch, Hopp, and Klaus () and Glaser et al () recently modelled the hydrological response using the 3D physically based model HydroGeoSphere (Therrien, McLaren, Sudicky, & Panday, ). The model reproduced the observed hydrograph well, but missed some specific features of the hydrograph, for example, peaks directly after dry conditions and the rise and recession of second, delayed peaks that are typical for the hydrological response at this site during wet conditions (Martínez‐Carreras et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The importance of preferential flow in soils for catchment‐scale TTDs may be difficult to evaluate. Glaser, Jackisch, Hopp, and Klaus (2019) showed in the Weierbach catchment (Luxembourg) that rainfall‐runoff simulations were not improved by modelling vertical preferential flow at the catchment scale, using the soil preferential flow parameters deduced from plot‐scale tracer breakthrough experiments. However, non‐uniform lateral flow (similar to lateral preferential flow) appeared to be an important mechanism for discharge generation in this catchment, and it could be implemented in the model by using a highly conductive horizontal soil layer (Glaser et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Glaser, Jackisch, Hopp, and Klaus (2019) showed in the Weierbach catchment (Luxembourg) that rainfall‐runoff simulations were not improved by modelling vertical preferential flow at the catchment scale, using the soil preferential flow parameters deduced from plot‐scale tracer breakthrough experiments. However, non‐uniform lateral flow (similar to lateral preferential flow) appeared to be an important mechanism for discharge generation in this catchment, and it could be implemented in the model by using a highly conductive horizontal soil layer (Glaser et al, 2019). Different conclusions regarding preferential flow were found by van Schaik et al (2014), who highlighted its non‐negligible role for runoff simulations during extreme rainfall events in a semi‐arid catchment in Spain.…”
Section: Discussionmentioning
confidence: 99%
“…This study is carried out in the Weierbach catchment, which has been the focus of an increasing number of investigations in the last few years about streamflow generation (Glaser et al, 2016(Glaser et al, , 2019bScaini et al, 2017Scaini et al, , 2018Carrer et al, 2019;Rodriguez and Klaus, in review), biogeochemistry (Moragues-Quiroga et al, 2017;Schwab et al, 2018), and pedology and geology (Juilleret et al, 2011;Gourdol et al, 2018). https://doi.org/10.5194/hess-2019-501 Preprint.…”
Section: Study Site Descriptionmentioning
confidence: 99%